South African Ebola diagnostic response in Sierra Leone: A modular high biosafety field laboratory. - Janusz T Paweska; Petrus Jansen van Vuren; Gunther H Meier; Chantel le Roux; Ousman S Conteh; Alan Kemp; Cardia Fourie; Prabha Naidoo; Serisha Naicker; Phumza Ohaebosim; Nadia Storm; Orienka Hellferscee; et al. (Public Library of Science (PLoS), 2017)
Background In August 2014, the National Institute for Communicable Diseases (NICD) in South Africa established a modular high-biosafety field Ebola diagnostic laboratory (SA FEDL) near Freetown, Sierra Leone in response to the rapidly increasing number of Ebola virus disease (EVD) cases. Methods and findings The SA FEDL operated in the Western Area of Sierra Leone, which remained a "hotspot" of the EVD epidemic for months. The FEDL was the only diagnostic capacity available to respond to the overwhelming demand for rapid EVD laboratory diagnosis for several weeks in the initial stages of the EVD crisis in the capital of Sierra Leone. Furthermore, the NICD set out to establish local capacity amongst Sierra Leonean nationals in all aspects of the FEDL functions from the outset. This led to the successful hand-over of the FEDL to the Sierra Leone Ministry of Health and Sanitation in March 2015. Between 25 August 2014 and 22 June 2016, the laboratory tested 11,250 specimens mostly from the Western Urban and Western Rural regions of Sierra Leone, of which 2,379 (21.14%) tested positive for Ebola virus RNA. Conclusions The bio-safety standards and the portability of the SA FEDL, offered a cost-effective and practical alternative for the rapid deployment of a field-operated high biocontainment facility. The SA FEDL teams demonstrated that it is highly beneficial to train the national staff in the course of formidable disease outbreak and accomplished their full integration into all operational and diagnostic aspects of the laboratory. This initiative contributed to the international efforts in bringing the EVD outbreak under control in Sierra Leone, as well as capacitating local African scientists and technologists to respond to diagnostic needs that might be required in future outbreaks of highly contagious pathogens.